Vieira Brandão´s Nationalism in his Tocata n°1 (Etude n° 4) for solo piano (Orfeu, 2017)
This text presents a discussion ofBrazilian composer José Vieira Brandão´s(1911-2002) attitudes towards the Braziliannationalist movement as well as his engagement with this trend as shown in his theoretical/analytical writings presented as aDocent Thesis in 1949. Brandãos´s posture is clearly expressed in his compositions.This particular analysis focuses on Tocatan° 1 (Etude n° 4) dedicated to Villa-Lobos,eminent representative of the nationalistmodernist aesthetics. Considering howclosely Brandão worked with Villa-Lobosas his preferred pianist, we aim at revealing shared sociocultural and musical concerns. With this purpose in mind, we evokeAgawu´s (2009) topics adapted to theanalysis of Latin American music by Plesch (1996) and to Brazilian music by Piedade (2013). Our analysis of this work seeksto reveal how Brandão´s “new aestheticstrends” (BRANDÃO, 1949) is a musical reification of the Brazilian nationalist ideology.Our reading of Brandão´s Tocata n°1 withits characteristic elements of Brazilian music, considers the work not only as a deeply felt homage to his mentor Villa-Lobosbut also as a legitimate representative ofthe political and artistic zeitgeist.
Keywords: José Vieira Brandão; Tocata 1; Brazilian Musicality; Nacionalism; Piano